STRATEGI PENGELOLAAN HUTAN TANAMAN INDUSTRI UNTUK MITIGASI PERUBAHAN IKLIM MELALUI SKEMA REDD+ - Ganjar Oki Widhanarto; Ris Hadi Purwanto; Ahmad Maryudi; . Senawi (Universitas Tanjungpura, 2018)
In 2009 the Goverment of Indonesia through the National Development Planning Agency has launched a Sectoral Climate Road Map, where the forestry sector relies on the development of industrial forest plantations (HTI) and forest management units (KPH) with the most efficient consideration of the cost budget and the effectiveness of technical feasibility for sustainability. The policy of HTI development by the Indonesian government furthermore has the opportunity to contribute to climate change mitigation through the REDD + scheme. This study aims to develop the strategies of industrial forest plantation management for REDD + schemes. This study analyzed internal factors that become strengths and weaknesses as well as external factors that become opportunities and threats using SWOT analysis to develop the strategies. The management of HTI in case of industrial forest plantation company PT. Finnantara Intiga (FI) was defined as an internal environment, while the external environment covers the entire environment related to HTI and REDD+. The results of the research showed that, the strength score is 1,817 and weakness is 1,186, so the difference is 0,631 (positive), as well as the element of opportunity is greater than the threat. The positive difference values both strength and opportunity indicate the priority strategies that will be used by PT. Finnantara Intiga in the REDD + scheme is an aggressive strategy (SO strategy)by using all the strengths and utilizing the opportunities.Keywords : Industrial forest plantation, REDD+, SWOT Analysis